2019
DOI: 10.1039/c8ra09710k
|View full text |Cite
|
Sign up to set email alerts
|

Co-amorphous palbociclib–organic acid systems with increased dissolution rate, enhanced physical stability and equivalent biosafety

Abstract: The preparation of co-amorphous drug systems by adding a small molecular excipient is a promising formulation in the modern pharmaceutical industry to improve the solubility, dissolution rate, and bioavailability of poorly soluble drugs. In this study, palbociclib co-amorphous systems with organic acids (succinic, tartaric, citric, and malic acid) at molar ratios of 1 : 1 were prepared by co-milling and characterized by differential scanning calorimetry (DSC), fourier transform infrared spectroscopy (FTIR) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 38 publications
(14 reference statements)
0
20
1
Order By: Relevance
“…However, thermal analysis showed that the CFX/TA (1:1) dispersions had a glass transition temperature (T g ) of 153.5°C. This is significantly higher than published data for amorphous CFX (87°C) and tartaric acid (24°C) ( 22 , 23 ). Such high T g compared to pure components suggests that the formed dispersion is co-amorphous salt.…”
Section: Resultscontrasting
confidence: 73%
“…However, thermal analysis showed that the CFX/TA (1:1) dispersions had a glass transition temperature (T g ) of 153.5°C. This is significantly higher than published data for amorphous CFX (87°C) and tartaric acid (24°C) ( 22 , 23 ). Such high T g compared to pure components suggests that the formed dispersion is co-amorphous salt.…”
Section: Resultscontrasting
confidence: 73%
“…Pal, Alp and the P(RGD) proteinoid NCs were characterized by FTIR ( Figure S2 ). The spectrum of Alp ( Figure S2A ) demonstrates typical peaks at 1400–1000 cm −1 corresponding to C–F vibration, 1317 cm −1 (C–S stretching band [ 53 ]), 1640 cm −1 (carbonyl stretching band), broad peaks at 2770–2870 cm −1 (C-H and CH 3 groups), and a peak at 3500 cm −1 corresponding to N–H stretching band [ 54 ]. The spectrum of Pal ( Figure S2B ) demonstrates typical peaks at 1900–1640 cm −1 corresponding to the carbonyl stretching band, 2780–2960 cm −1 (C–H and CH 3 stretching band [ 55 ]) and 3500 cm −1 (N–H stretching band [ 54 ]).…”
Section: Resultsmentioning
confidence: 99%
“…The spectrum of Alp (Figure S2A) demonstrates typical peaks at 1400-1000 cm −1 corresponding to C-F vibration, 1317 cm −1 (C-S stretching band [53]), 1640 cm −1 (carbonyl stretching band), broad peaks at 2770-2870 cm −1 (C-H and CH 3 groups), and a peak at 3500 cm −1 corresponding to N-H stretching band [54]. The spectrum of Pal (Figure S2B) demonstrates typical peaks at 1900-1640 cm −1 corresponding to the carbonyl stretching band, 2780-2960 cm −1 (C-H and CH 3 stretching band [55]) and 3500 cm −1 (N-H stretching band [54]). The spectrum of P(RGD) (Figure S2C) demonstrates typical peaks of proteinoids [21,50] at 660 and 770 cm −1 (amine N-H wagging [56]) belonging to the arginine side chain, which possesses three atoms of nitrogen.…”
Section: Ftir Analysis Of the Free Drugs And P(rgd) Proteinoid Ncsmentioning
confidence: 99%
“… 6 For example, the limited miscibility of the drug with the polymer sometimes requires the addition of a large amount of polymer, which is disadvantageous for the usability, manufacturing, and cost. 7 Besides, ASDs also have problems of poor long-term stability as well as difficulty in manufacturing and processing. 8 Co-amorphous systems have been extensively studied in the pharmaceutical industry because of their excellent properties, such as promoting drug solubilization, enhancing drug stability, and improving drug delivery and absorption.…”
Section: Introductionmentioning
confidence: 99%